DNA Damage Protection for Enhanced Bacterial Survival Under Simulated Low Earth Orbit Environmental Conditions in Escherichia coli - Puig, Jaume; Knödlseder, Nastassia; Quera, Jaume; Algara, Manuel; Güell, Marc (Frontiers in Microbiology, 2021)
Some organisms have shown the ability to naturally survive in extreme environments, even outer space. Some of these have natural mechanisms to resist severe DNA damage conditions such as ionizing and non-ionizing radiation, extreme temperatures and low pressures. A good example can be found in Deinococcus radiodurans, which was exposed to severe conditions such as those listed in the Exposure Facility of the International Space Station (ISS) for up to three years. Another example are tardigrades (Ramazzottius varieornatus) which are some of the most resilient animals known. In this study, the survival under simulated ISS environmental conditions was tested in Escherichia coli. The radiation resistance of this bacteria was enhanced using the Dsup gene from R. varieornatus, and two more genes from D. radiodurans involved in DNA damage repair were tested. The enhanced survival to wide ranges of temperatures and low pressures was then tested in the new strains. This research constitutes a first step in the creation of new bacterial strains engineered to survive severe conditions and adapting existing species for their survival on remote environments, including extra-terrestrial habitats. In addition, studying the efficacy and the functioning of the genetic mechanisms used in this study could be beneficial for medical and life sciences engineering.